Numerical modeling of aluminum alloy AW5083using large strain thermo-elasto-plasticity - Sobierańska, Agnieszka; Wcisło, Balbina (Engineering Transactions, 2025)
This paper deals with the constitutive modeling and finite element simulations of advanced models related to large strain thermo-elasto-plastic behavior of aluminum alloy AW5083, which can reproduce the material response at different temperatures from room temperature up to 500 degrees Celsius. Significant focus is placed on the internal sources of cooling and heating resulting from thermo-elastic and thermo-plastic couplings, respectively, and the influence of elevated temperature on couplings. The formulation of the constitutive description is based on the thermodynamic approach. Two models are presented and tested: including temperature-dependent and temperature-independent plastic free energy function. Numerical tests of the developed models are carried out for a uniaxial tension test. For the sake of comparison with experimental results, a dogbone specimen examined in a tensile machine is analyzed.